Penatalaksanaan Fisioterapi PadaPost Repaired Anterior Crusiatum Ligament SinistraDi Rsal Ramelansurabaya - , Darmadi (2016)
Background: Anterior Cruciate Ligament (ACL) is the most commonly injured ligament in the knee. ACL is a major cause of sport activities for example football or basketball, one diagnose can be established of the patient Anterior Cruciate Ligament is Active Assisted Exercise and Hold Relax. Objective: To know the benefits or infrared and therapy exercise against spasms reduction, pain reduction and improvement in muscle strength increase range of motion so as improve functional ability in the case of post repair anterior cruciate ligament sinistra. Methods: Giving modality infrared rays and exercise therapy using active and hold relax. Results : After treatment, obtained result T1 - T6 is pain reduction assessed by Visuals Analog Scale (VAS), followed by an increase range of motion using geneometer, increase in muscle strength assessed with Manual Muscle Testing (MMT) so which can lead to a decrease in oedema evidenced by measurement athropometri with mid line. Conclusions: Giving post repair anterior cruciate ligament sinistra infrared and exercise therapy showed a reduction of pain, increased muscle strength and decrease oedema.